THE INFLUENCE OF FOREIGN CULTURE ON REGIONAL LANGUAGES IN NORTH SUMATRA - Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (Sean Institute, 2023)
This study aims to determine the condition of the regional language and culture in North Sumatra with the inclusion of foreign cultures which are now very easy to access. In addition, this research also aims to see the condition of the shift in regional languages among the people in North Sumatra. Furthermore, it will be seen about the role of the community in overcoming these problems. This research was conducted in the province of North Sumatra using a quantitative-qualitative descriptive method. And this data collection technique was carried out by means of observation, questionnaires, and also interviews which were equipped with documentation and also research instruments consisting of recording and recording. The results of the study will show the conditions of language shift that exist in the province of North Sumatra. The use of language starts from the family environment and also in educational settings such as schools and also in the community environment amid the onslaught of foreign cultures that entered North Sumatra. From this research it is hoped that it can be an option to overcome the influx of foreign cultures and also their influence on regional languages in North Sumatra.